Transcatheter Aortic Valve Implantation with balloon-expandable valve in low-flow low-gradient severe aortic stenosis in Nepal - Adhikari, Chandra Mani; Timalsena, Birat Krishna; Bogati, Amrit; Khan, Barkadin; Acharya, Anjana; Ghimire, Vijay; Mehta, Kshitij; Prajapati, Dipanker (Nepalese Heart Journal, 2023)
Transcatheter aortic valve implantation is the most preferred treatment of aortic stenosis in elderly patients at high surgical risk; however, few data exist on the adoption of transcatheter aortic valve implantation for the management of low-flow, low-gradient severe aortic stenosis patients. We present a recent case experience with a 77-year-old man suffering from low-flow, low-gradient, symptomatic severe aortic stenosis with concomitant coronary artery lesions in the left anterior descending and right coronary arteries. He was treated successfully with balloon-expandable transcatheter aortic valve implantation after the percutaneous coronary intervention of the left anterior descending artery and right coronary artery lesion. Post-procedural and 30-day follow-ups showed good functional and hemodynamic improvements with the mean aortic gradient of 3 mmHg (baseline: 30 mmHg) without residual paravalvular leakage. Our first experience with a balloon-expandable transcatheter valve was satisfactory as we observed clinical efficacy and good performance of the balloon-expandable transcatheter aortic valve in low-flow, low-gradient, symptomatic severe AS patients.